Perioperative management of patients undergoing spine surgery: a survey of spine surgeons and a non-systematic review of the literature - V.B. Lebedev; B.R. Kinzyagulov; D.S. Epifanov; A.A. Zuev (Хирургия позвоночника)
Objective. To assess trends in the management of patients after surgical treatment for degenerative diseases of the spine and to analyze literature data on perioperative management of this category of patients. Material and Methods. An anonymous online survey of 55 spine surgeons was conducted on the specifics of management of patients operated on for spinal stenosis and intervertebral disc herniation using microsurgical and endoscopic methods. The results of the survey were analyzed along with relevant literature data to provide a comprehensive understanding of the current practices in this field. Results. The analysis of questionnaires showed that there are significant differences and contradictions among surgeons regarding the use of antibiotics, restrictions on sitting after surgery, length of hospital stay, and use of a lumbar orthosis. A review of the world and domestic literature revealed a sufficient evidence of some studies to support their use as recommendations, while there is still a lack of evidence for most of the issues raised. Conclusion. Existing statements and protocols for the treatment of patients undergoing spine surgery need to be improved; randomized studies are required to establish the optimal approach for perioperative management of this group of patients.